MLL-SEPT5 Fusion Transcript in Myelodysplastic Syndrome Patient With t(11;22)(q23;q11) - Zou, Duobing; Chen, Ying; Wu, Ningning; Zhang, Yi; Ouyang, Guifang; Mu, Qitian (Frontiers in Medicine, 2021)
Objectives: This study aimed to identify unknown MLL translocation partner genes in a de novo myelodysplastic syndrome (MDS) patient with t(11;22)(q23;q11), and investigate the clinical and molecular features of this patient. Methods: Karyotype analysis of bone marrow cells was carried out to reveal the chromosomal abnormalities. FISH was performed to detect MLL gene rearrangement using a MLL-specific break apart probe. LDI-PCR and RT-PCR were performed, and the PCR products were sequenced using an Illumina MiSeq sequencer. Then the sequence data of the PCR products were analysed using bioinformatics tools. Meanwhile, clinical data were collected to evaluate the prognosis of the patient. Results: Chromosomal karyotype analysis showed that the karyotype of the patient was 46, XX, t(11;22)(q23;q11)[10]/46, XX[1]. Subsequently, FISH results confirmed MLL gene rearrangement in the patient. LDI-PCR precisely showed that SEPT5 was the MLL translocation partner gene. RT-PCR and sequencing analysis disclosed the presence of MLL-SEPT5 fusion transcript and confirmed the fusion between MLL exon 8 and SEPT5 exon 3. Moreover, the patient had a recurrence shortly after allogeneic hematopoietic stem cell transplantation. Conclusions: Although the MLL-SEPT5 fusion transcript was occasionally described in acute myeloid leukemia (AML), it was first identified in MDS. Patients with MLL-SEPT5 fusion gene exhibited a poor prognosis even with aggressive treatment.